Role of very short-term intravenous hydrocortisone in reducing postdural puncture headache - Md Rabiul Alam; Md Aminur Rahman; Reza Ershad (Wolters Kluwer Medknow Publications, 2012)
Objective: Headache is not an uncommon complication of spinal anesthesia. The efficacy of intravenous (IV) hydrocortisone in treating the patients with postdural puncture headache was observed in this study. Materials and Methods: Sixty patients with headache following spinal anesthesia were randomly allocated into two groups. Thirty patients received only conventional therapy (recumbent positioning, IV or oral hydration, analgesics with caffeine, stool softeners, and soft diet) plus 2 ml of normal saline IV (placebo) 8 hourly for 48 h. Thirty other patients received conventional therapy plus hydrocortisone IV (100 mg in 2 ml 8 hourly for 48 h). Headache intensity was measured using visual analogue scale. Results: No significant difference was observed in baseline headache intensity between the two groups (P = 0.6642) before beginning of treatment. After 6 h, the mean headache intensity in patients treated conventionally was 6.02 ± 2.46, while it was 2.06 ± 1.98 in other patients who received additional hydrocortisone IV (P < 0.0001). After 24 h, headache intensity was 3.77 ± 1.85 in conventionally treated group versus 0.94 ± 2.67 in hydrocortisone group (P < 0.0001), while it was 1.95 ± 1.12 in conventionally treated group versus 0.69 ± 1.64 in hydrocortisone group (P = 0.001) after 48 h. Conclusions: Very short-term use of IV hydrocortisone was found effective in reducing headache following spinal anesthesia. However, its clear mechanism of action is yet to be determined. Large-scale studies are recommended to consider the steroid therapy as a standard treatment for postdural puncture headache.